Benefit Management Framework : Realizing benefits from IT project implemenation - Sidikova, Mashhura (My University, 2018)
Information Technology has become fundamental part of modern company due to its potential to improve performance both on strategic and operational levels (Ashurst, 2015), stressing the importance of IT project implementation’s success on achieving organizational strategy. But due to complexity and issues during the implementation phase their target shifts to making the IT tool operational instead of realizing core goals which have been set initially (Scheurwater and De Swaan, 2009). The main goal of this research is to study benefits management of IT project deployment. The purpose is to develop a framework of benefits management to be used for IT project’s successful implementation. In order to do so, there were number of areas to cover. First, it was important to find out what type of benefits management tools are out there by doing review of literature. Since the aim has been to gain benefits from IT project, their critical factors were studied in literature review. Second, it was important to examine in case study their usage. Literature review and analysis of case study guided to develop a plan on how to improve benefit management for IT project implementation. The objective has been to look at benefit management framework from organization’s perspective and its strategy, from company’s perspective which invests in project to gain return on their investment. In this study, the strategy has been doing exploratory research through in-depth interviews, participant observation, document analysis and also surveys. The goal of this study has been to create a benefit management framework for IT project implementation by integrating theory and case study. Theoretical framework created from doing literature review applied in case company study to ensure surveys, interviews and researcher’s own observations are within the area of topic being studied. The framework developed from review of literature identified focus of majority of scientific articles, books and other publications in topic of benefit management on initiation phase. Number of publications of articles and books decrease in study of post implementation benefit management, and very limited for phases between initiation and post implementation. Findings of the research highlighted the importance of benefits management activities in organization throughout the process of IT project deployment and supported theory that with proper project governance, organization change management, and support from senior management, realizing benefits from IT project is realistic.
Keywords: Benefit Management, Benefit Realization, Project Management, Change Management, Information Technology